The Role Of Multi-Stakeholder Collaboration In Flood Disaster Management System In Bekasi: A Critical Review Of Response And Recovery - Tubagus Ryan Aronda; Setya Haksama; Yohanes Ary Prayoga (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to critically analyse the role of multi-stakeholder collaboration in Bekasi's flood disaster management system, focusing on response and recovery following the March 2025 flood. Using a qualitative approach with a literature review method, this study examines various policy documents, official reports, academic studies, and media sources related to flood management. The findings indicate that although a formal collaboration framework exists, implementation in the field still faces challenges such as government institutional dominance, resource imbalances, and a lack of precise coordination mechanisms. Collaboration primarily focuses on response and recovery, while mitigation and preparedness receive less attention. Additionally, community participation in evacuation and cleanup efforts demonstrates the potential for development under the Community-Based Disaster Management (CBDM) approach, but engagement in planning and evaluation remains limited. This study recommends enhancing collaborative capacity, strengthening cross-sectoral coordination mechanisms, and integrating all phases of the disaster management cycle to improve the effectiveness of a more adaptive and responsive disaster risk management system in the future.